Oil Wealth and Development in Uganda and Beyond: - Langer, Arnim; Ukiwo, Ukoha; Mbabazi, Pamela (Leuven University Press, 2020)
With an increasing number of African countries having discovered commercially viable quantities of oil and gas in recent years, including, for example, Kenya, Chad, Ghana and Uganda, there is both excitement and trepidation about the prospects for increased incomes and investments, economic growth and development on the continent. This is due to comparative historical evidence of the link between natural resource exploitation, economic growth and development on the one hand and natural resource exploitation, economic decline and socio-political crises on the other hand (see, for example, Ross, 2003; 2012; Sachs and Warner, 2001; Torres, Afonso and Soares, 2012). Indeed, a substantial body of empirical studies has shown that many countries ‘blessed’ with natural resources have paradoxically faced economic decline and severe socio-political crises (see, for example, Mehlum, Moene and Torvik, 2006; Ross, 2012; Sachs and Warner, 1995).
Prospects, Opportunities and Challenges.
This book was Edited by Arnim Langer, Ukoha Ukiwo and Pamela Mbabazi.With an increasing number of African countries having discovered commercially viable quantities of oil and gas in recent years, including, for example, Kenya, Chad, Ghana and Uganda, there is both excitement and trepidation about the prospects for increased incomes and investments, economic growth and development on the continent.
Keywords: Oil ,Wealth, Development,Uganda , Prospects,Opportunities , Challenges.